Deep Proteomic Insights into the Individual Short‐Term Pellicle Formation on Enamel—An In Situ Pilot Study. Issue 3 (28th April 2020) - Trautmann, Simone; Künzel, Nicolas; Fecher‐Trost, Claudia; Barghash, Ahmad; Schalkowsky, Pascal; Dudek, Johanna; Delius, Judith; Helms, Volkhard; Hannig, Matthias
Abstract : Purpose: Dental pellicle formation starts instantaneously after oral hygiene due to the adsorption of salivary proteins to all orally exposed surfaces. The pellicle acts as a physiological mediator, protects the tooth surface from mechanical damages and reduces acid‐induced enamel demineralization. The aim of this pilot study is to identify and characterize individual proteomic profiles of the initial pellicle formed on dental enamel and to compare the profiles with the corresponding saliva to analyze specific adsorption patterns occurring during pellicle formation. Experimental Design: The 3‐min pellicle of five subjects formed in situ on bovine enamel is eluted chemically and analyzed separately by nano‐mass spectrometry. The analysis of the corresponding saliva is conducted in parallel. Results: Up to 498 pellicle proteins and up to 1032 salivary proteins are identified on an individual level. Comparison of the salivary and pellicle protein profiles demonstrates the pellicle formation to be highly individual. Nineteen proteins are significantly enriched in the 3‐min pellicle of all subjects and 22 proteins are significantly depleted indicating that pellicle formation relies on selective adsorption. Conclusions and Clinical Relevance: The short‐term enamel pellicle is composed of several hundreds of adsorbed salivary proteins and reveals a highly individual proteomic profile.